2018
DOI: 10.2174/1871520617666170327105706
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Inhibitors of Phosphatidylinositol-3-Kinase (PI3K) Pathway: Anticancer Potential of Aroma Compounds of Plant Essential Oils

Abstract: Methyl nonanoate, (R)-citronellol, cis-carveol (L-carveol), 3-methyl-Cyclohexanone, 4-carene and thujopsene were finally screened for PI3K targeted anti-cancer therapies which may find direct application as inhalers or sprays against lung cancer as these compounds are highly volatile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…GC‐MS study of the oils showed the presence of δ‐cadinene, β‐caryophyllen, δ‐elemen, δ‐carene, α and β‐pinene and δ‐3‐carene predominantly. These constituents have been reported to possess anticancer activities (Bordoloi et al, ; Dahham et al, ; Guan et al, ; Hui et al, ; Montanari et al, ; Ramos et al, ; Wang et al, ). The cytotoxic activity of the present study may be due to those components present in the oils.…”
Section: Resultsmentioning
confidence: 99%
“…GC‐MS study of the oils showed the presence of δ‐cadinene, β‐caryophyllen, δ‐elemen, δ‐carene, α and β‐pinene and δ‐3‐carene predominantly. These constituents have been reported to possess anticancer activities (Bordoloi et al, ; Dahham et al, ; Guan et al, ; Hui et al, ; Montanari et al, ; Ramos et al, ; Wang et al, ). The cytotoxic activity of the present study may be due to those components present in the oils.…”
Section: Resultsmentioning
confidence: 99%
“…Plant volatiles transmit signaling within and between plants [28]. Some papers showed that volatile compounds from leaves and fruits have a novel source of anticancer drugs [29][30][31]. We wanted to find plant VOCs killing breast cancer stem cells and start screening the VOCs against breast CSC formation using 15 plant VOCs.…”
Section: Discussionmentioning
confidence: 99%
“…Another compound observed to inhibit the growth of cancer cells is cedrol (IC 50 = 44.36 ± 0.9 μg/ml toward C32 human amelanotic melanoma cells; 41.06 ± 0.7 μg/ml toward ACHN human renal cell adenocarcinoma cells), which was shown to increase intracellular ROS production and induce autophagy and apoptotic cell death through the PI3K/Akt signaling pathway in A549 non-small cell lung carcinoma cells [35,36]. Furthermore, thujopsene, a common component in plant extracts, notably inhibited the proliferation of A549 cells (IC50 = 35.27 μg/ml) by decreasing AKT/mTOR protein expression [37]. Many plant extracts or oils, such as Salvia officinalis L. and Xylopia laevigata, contain γ-muurolene and have reported anti-cancer activities [38].…”
Section: Discussionmentioning
confidence: 99%